2016
DOI: 10.1007/s12250-016-3723-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two cleavage fragments from the Aquareovirus nonstructural protein NS80

Abstract: Aquareovirus species vary with respect to pathogenicity, and the nonstructural protein NS80 of aquareoviruses has been implicated in the regulation of viral replication and assembly, which can form viral inclusion bodies (VIBs) and recruit viral proteins to its VIBs in infected cells. NS80 consists of 742 amino acids with a molecular weight of approximately 80 kDa. Interestingly, a short specific fragment of NS80 has also been detected in infected cells. In this study, an approximately 58-kDa product of NS80 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Similar to other reoviruses, GCRV consists of an 11-segment dsRNA genome core surrounded by a double-layered icosahedral particle, with an overall diameter of approximately 75-80 nm. The 11-segment dsRNA genome encodes seven structural (VP1-VP7) and five nonstructural (NS16, NS26, NS31, NS38, and NS80) proteins (Chen et al 2016). Phylogenic analysis indicated that aquareoviruses have a close evolutionary relationship with orthoreoviruses (Attoui et al 2002;Fang et al 2000).…”
mentioning
confidence: 99%
“…Similar to other reoviruses, GCRV consists of an 11-segment dsRNA genome core surrounded by a double-layered icosahedral particle, with an overall diameter of approximately 75-80 nm. The 11-segment dsRNA genome encodes seven structural (VP1-VP7) and five nonstructural (NS16, NS26, NS31, NS38, and NS80) proteins (Chen et al 2016). Phylogenic analysis indicated that aquareoviruses have a close evolutionary relationship with orthoreoviruses (Attoui et al 2002;Fang et al 2000).…”
mentioning
confidence: 99%